1989
DOI: 10.1111/j.1528-1157.1989.tb05291.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the International League Against Epilepsy Proposals for Classification of Epileptic Seizures and the Epilepsies and Epileptic Syndromes in a Pediatric Outpatient Epilepsy Clinic

Abstract: The International League Against Epilepsy proposals for classification of epileptic seizures (1981) and of the epilepsies and epileptic syndromes (1985) have been used in daily practice in a pediatric epilepsy clinic in Bogota, Colombia. Most patients can be classified by these schemes, and the classifications are useful in everyday diagnosis and management. However, there are some drawbacks and difficulties with the classifications. Some syndromes are unnecessarily separated as different entities, artificiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(24 citation statements)
references
References 13 publications
3
19
1
1
Order By: Relevance
“…Many of the patients included in such studies performed thus far have epilepsies which have been presumed to be symptomatic, although, frequently, no exact cause has been identified. The ICEES can be successfully applied in studies in developing countries, as several authors have shown [11, 15, 18, 21, 22], but whether the high classifiable proportions have amounted to clinically or epidemiologically useful information is debatable. A less detailed epilepsy classification based upon risk factors for epilepsy would surely be preferable for such studies [6].…”
Section: Use Of the Icees In Population-based Studies Of Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the patients included in such studies performed thus far have epilepsies which have been presumed to be symptomatic, although, frequently, no exact cause has been identified. The ICEES can be successfully applied in studies in developing countries, as several authors have shown [11, 15, 18, 21, 22], but whether the high classifiable proportions have amounted to clinically or epidemiologically useful information is debatable. A less detailed epilepsy classification based upon risk factors for epilepsy would surely be preferable for such studies [6].…”
Section: Use Of the Icees In Population-based Studies Of Epilepsymentioning
confidence: 99%
“…Some studies relying on EEG departments for case ascertainment [10, 20]may have underrepresented or even excluded patients in whom EEG was considered inappropriate or technically difficult (e.g., the elderly or patients with severe learning difficulty) or those with seizures associated with an important co-existent pathology (e.g., stroke, brain tumour). Clearly, the reason that so many of these studies have been performed in hospital settings [11, 12, 14, 15, 16, 18, 19, 21, 22, 23, 24, 25, 26]is that this environment confers better access to those investigations facilitating successful classification, hence reducing the proportion with cryptogenic or unclassifiable epilepsies. Additionally, many of these studies have been retrospective in design, resulting in incomplete case ascertainment and data collection and a large interpatient variation in the extent of investigation [27].…”
Section: Use Of the Icees In Population-based Studies Of Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of other underlying structural lesions or metabolic anomalies, the International Classification of Epilepsies and Epileptic Syndromes, approved in 1989 by the International League Against Epilepsy, distinguished between idiopathic and cryptogenic epilepsy [Eslava-Cobos and Nariño, 1989]. Within idiopathic epilepsies, the idiopathic generalized epilepsies are characterized by recurrent unprovoked generalized seizures with synchronous alterations detected by EEG, encompassing ∼ 30% of all epilepsies .…”
mentioning
confidence: 99%
“…The clinical application of ICEES had been tested by many investigators (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and a majority of them approved its usefulness by demonstrating that they could classify almost all of their patients into the diagnostic categories of ICEES. Berg et al (13) also reported a good interrater agreement.…”
mentioning
confidence: 99%